A role for doctors in assisted dying? An analysis of legal regulations and medical professional positions in six European countries. Issue 1 (21st December 2007) - Bosshard, G; Broeckaert, B; Clark, D; Materstvedt, L J; Gordijn, B; Müller-Busch, H C
Abstract : Objectives: To analyse legislation and medical professional positions concerning the doctor's role in assisted dying in western Europe, and to discuss their implications for doctors. Method: This paper is based on country-specific reports by experts from European countries where assisted dying is legalised (Belgium, The Netherlands), or openly practiced (Switzerland), or where it is illegal (Germany, Norway, UK). Results: Laws on assisted dying in The Netherlands and Belgium are restricted to doctors. In principle, assisted suicide (but not euthanasia) is not illegal in either Germany or Switzerland, but a doctor's participation in Germany would violate the code of professional medical conduct and might contravene of a doctor's legal duty to save life. The Assisted Dying for the Terminally Ill Bill proposed in the UK in 2005 focused on doctors, whereas the Proposal on Assisted Dying of the Norwegian Penal Code Commission minority in 2002 did not. Professional medical organisations in all these countries except The Netherlands maintain the position that medical assistance in dying conflicts with the basic role of doctors. However, in Belgium and Switzerland, and for a time in the UK, these organisations dropped their opposition to new legislation. Today, they regard the issue as primarily a matter for society and politics. This "neutral" stance differs from the official position of the Royal Dutch Medical Association which has played a key role in developing the Dutch practice of euthanasia as a "medical end-of-life decision" since the 1970s. Conclusion: A society moving towards an open approach to assisted dying should carefully identify tasks to assign exclusively to medical doctors, and distinguish those possibly better performed by other professions.